Flexural behavior of high ductility MPC-based composites under low-temperature curing. (20th September 2021) - Feng, Hu; Nie, Shuang; Guo, Aofei; Shen, Shihao; Gao, Danying; Chen, Gang
Highlights: The flexural behavior of HDMC under low-temperature curing was studied. Effect of FA content on flexural behavior of HDMC was examined. Effect of PVA fiber volume fraction on flexural behavior of HDMC was examined. Effect of sand to binder ratio on flexural behavior of HDMC was examined. Effect of water to solid ratio on flexural behavior of HDMC was examined. Abstract: A high ductility magnesium phosphate cement-based composites (HDMC) was developed using polyvinyl alcohol (PVA) fibers and fly ash. In cold areas or winter, there is a need for the urgent strengthening and repair of concrete structures by using the HDMC, so the performance of the HDMC in low temperature environment needs to be explored to expand its application. In this study, the flexural behavior of HDMC under low-temperature curing was evaluated through the flexural test. The effects of fly ash (FA) content, sand/binder mass ratio (S/B), water/solid mass ratio (W/S), PVA fiber volume fraction ( Vf ), curing age, and curing temperature on the flexural behavior of the HDMC were examined. The results showed that as the FA content increased, the strength of the HDMC was gradually reduced, and the toughness and ductility exhibited the best at 30%. As the S/B increased, the strength, toughness, and ductility of the HDMC first increased up to the S/B of 0.2 and then decreased. With the increase of W/S, the toughness and especially the ductility of the HDMC were significantly improved, whereas the strength was reduced slightly. Also, the increase of Vf could improve the strength, toughness, and ductility of the HDMC. Generally, the HDMC mixture with 30% FA, 0.2 S/B, 0.14 W/S, and 2.0% Vf was the best. Besides, as the curing age increased, the toughness and ductility first increased and then decreased; and the strength and toughness could be higher when cured at 0 °C than −5 °C.